Patchouli Farmers Strategy For Business Development In Meranti Tengah Village, Toba Samosir Regency) - Nicholas Marpaung; Feby Aulia Safrin (Integrated Journal of Business and Economics (IJBE), 2020)
This research aims to determine the strategy of business development of patchouli oil farmers in improving economic welfare, to analyzing obstacles or barriers in running the cultivation and production of patchouli oil in central Meranti The district of Pintu Pohan Meranti Toba Samosir Regency. This type of research is descriptive research with a qualitative approach because the research intends to understand what phenomena experienced by the subject of research. The method of determining the area of the research use Purposive technique or deliberate with consideration of Central Meranti is one of the villages that the majority of its citizens still hang the livelihood as a patchouli oil farmer. Data collection methods are obtained from primary data and secondary data where primary data is obtained through interviews with Informans as well as direct observations of the field, and secondary data is obtained from the relevant agencies. The Data obtained is then analyzed using SWOT analysis. The results showed that there were only 2 families that still maintain patchouli oil farming efforts with patterns and strategies to develop this business in a simple way. Patchouli marketing is also do by selling directly due to price fluctuations that happen very often. In addition, the limited information such as the writing and socialization of a patchouli is still very limited from the government to the farmers so that more and more farmers are switching commodities.